2022
DOI: 10.2147/jaa.s366014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Traps: A Novel Therapeutic Target for Severe Asthma

Abstract: Asthma is a complicated disease defined by a combination of clinical symptoms and physiological characteristics. Typically, asthma is diagnosed by the presence of episodic cough, wheezing, or dyspnea triggered by variable environmental factors (allergens and respiratory infections), and reversible airflow obstruction. To date, the majority of asthmatic patients have been adequately controlled by anti-inflammatory/bronchodilating agents, but those with severe asthma (SA) have not been sufficiently controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“… 32 Eosinophil extracellular trap (EET) which is released from activated eosinophils contains a mixture of web‐like DNA fibers and granule proteins. 33 EET‐forming eosinophil counts were positively correlated with serum EDN levels and negatively correlated with FEV 1 % in patients with SA. 34 In this context, EET and EDN have been postulated to be involved in the mechanism of activated eosinophils and potential therapeutic target for AERD.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 32 Eosinophil extracellular trap (EET) which is released from activated eosinophils contains a mixture of web‐like DNA fibers and granule proteins. 33 EET‐forming eosinophil counts were positively correlated with serum EDN levels and negatively correlated with FEV 1 % in patients with SA. 34 In this context, EET and EDN have been postulated to be involved in the mechanism of activated eosinophils and potential therapeutic target for AERD.…”
Section: Discussionmentioning
confidence: 92%
“…As AERD is not fully understood by enhanced production of type 2 cytokines or cysteinyl leukotrienes, novel molecules related to activated eosinophils have been proposed to be implicated in AERD pathogenesis 32 . Eosinophil extracellular trap (EET) which is released from activated eosinophils contains a mixture of web‐like DNA fibers and granule proteins 33 . EET‐forming eosinophil counts were positively correlated with serum EDN levels and negatively correlated with FEV 1 % in patients with SA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that IL-5 can stimulate eosinophils to release EETs in a ROS-dependent manner [ 32 ]. Furthermore, in patients with severe eosinophilic asthma, peripheral blood eosinophils exhibit enhanced release of EETs when co-stimulated with IL-5 and LPS [ 93 ], suggesting that elevated levels of IL-5 in vivo may play an important role in the pathogenesis of severe eosinophilic asthma [ 94 ].…”
Section: Therapeutic Targets For Eetsmentioning
confidence: 99%
“…As such, NETs have been implicated in the pathogenesis of asthma in adults. Indeed, both NETs and eosinophil extracellular traps (EETs) seem to be implicated in persistent asthma [ 27 ]; however, the aspects of these mechanisms remain understudied. In particular, the protein profile of NET structures, which is determined by the disease microenvironment, is not known, and NETosis in severe childhood asthma remains a scientific puzzle.…”
Section: Introductionmentioning
confidence: 99%